Quantification of phosphoinositides reveals strong enrichment of PIP 2 in HIV-1 compared to producer cell membranes - Mücksch, Frauke; Lüchtenborg, Christian; Glass, Bärbel; Schultz, Carsten; Brügger, Britta; Kräusslich, Hans-Georg (Scientific reports, 2019)
Human immunodeficiency virus type 1 (HIV-1) acquires its lipid envelope during budding from the plasma membrane of the host cell. Various studies indicated that HIV-1 membranes differ from producer cell plasma membranes, suggesting budding from specialized membrane microdomains. The phosphoinositide PI(4,5)P2 has been of particular interest since PI(4,5)P2 is needed to recruit the viral structural polyprotein Gag to the plasma membrane and thus facilitates viral morphogenesis. While there is evidence for an enrichment of PIP2 in HIV-1, fully quantitative analysis of all phosphoinositides remains technically challenging and therefore has not been reported, yet. Here, we present a comprehensive analysis of the lipid content of HIV-1 and of plasma membranes from infected and non-infected producer cells, resulting in a total of 478 quantified lipid compounds, including molecular species distribution of 25 different lipid classes. Quantitative analyses of phosphoinositides revealed strong enrichment of PIP2, but also of PIP3, in the viral compared to the producer cell plasma membrane. We calculated an average of ca. 8,000 PIP2 molecules per HIV-1 particle, three times more than Gag. We speculate that the high density of PIP2 at the HIV-1 assembly site is mediated by transient interactions with viral Gag polyproteins, facilitating PIP2 concentration in this microdomain. These results are consistent with our previous observation that PIP2 is not only required for recruiting, but also for stably maintaining Gag at the plasma membrane. We believe that this quantitative analysis of the molecular anatomy of the HIV-1 lipid envelope may serve as standard reference for future investigations.
Gesehen am 15.01.2020